Piriformospora indica based elicitation for overproduction of phenolic compounds by hairy root cultures of Ficus carica - Amani, Shahla; Mohebodini, Mehdi; Khademvatan, Shahram; Jafari, Morad; Kumar, Vinod (Elsevier, 2020)
Ficus carica L. is an important source of phenolic and flavonoid compounds with valuable pharmaceutical application across various diseases. The current study was carried out to investigate the influence of Piriformospora indica elicitation on growth, production of phenolic compounds, antioxidant capacity, and expression level of flavonoid biosynthetic pathway genes in hairy root (HR) cultures of F. carica. The maximum improvement in accumulation of phenolic compounds was observed when HR culture of Ficus carica L. was exposed to 2% culture filtrate of P. indica for 72 h: gallic acid (80.5- fold), caffeic acid (26.2-fold), coumaric acid (4.5-fold), and cinnamic acid (60.1-fold), apigenin (27.6-fold) and rutin (5.7-fold). While the highest levels of chlorogenic acid (4.9-fold) and quercetin flavonoid (8.8-fold) were obtained after 48 h elicitation with culture filtrate and cell extract of P. indica at 6% (v/v), respectively. The analysis of biosynthetic genes revealed that the exposure to fungal elicitors resulted in up-regulation of phenylalanine ammonia-lyase (PAL), chalcone synthase (CHS), UDP-glucose flavonoid 3-O-glucosyltransferase (UFGT) and MYB3 transcription factor. This study shows the potential of P. indica as an efficacious elicitor for enhancing the secondary metabolites production by F. carica HRs.
Keywords: Ficus carica L.; Fungal elicitor; Phenolic compounds; Piriformospora indica; Elicitation; Gene expression